2017
DOI: 10.1080/00140139.2017.1316018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing user acceptance towards automated and conventional sink use for hand decontamination using the technology acceptance model

Abstract: Hand hygiene (HH) prevents harmful contaminants spreading in settings including domestic, health care and food handling. Strategies to improve HH range from behavioural techniques through to automated sinks that ensure hand surface cleaning. This study aimed to assess user experience and acceptance towards a new automated sink, compared to a normal sink. An adapted version of the technology acceptance model (TAM) assessed each mode of handwashing. A within-subjects design enabled N = 46 participants to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…TAM models have revealed their ability to explain the differences between technology usage and behaviour across different contexts (Al-Okaily et al 2020c;Baptista and Oliveira 2016;Chen et al 2019;Dawson et al 2017).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…TAM models have revealed their ability to explain the differences between technology usage and behaviour across different contexts (Al-Okaily et al 2020c;Baptista and Oliveira 2016;Chen et al 2019;Dawson et al 2017).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…TAM models are consistently shown to be able to explain a large amount of variance in technology usage and acceptance behavior across varied contexts. 3136 While the models have been widely tested, validated and extended in health informatics applications used by medical professionals, 3739 they have seldom been applied to the modeling of consumer acceptance of health informatics applications. 15,40,41 In fact, consumers’ acceptance may be different from that of professionals, 42 as consumers are more likely to encounter difficulties in using health informatics applications due to their lack of self-efficacy and usability issues.…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Ghazizadeh, et al [52] proposed an automation acceptance model (AAM) which included trust as a crucial contributor to explain user acceptance of automation technology. Previous studies have used trust to explain technology acceptance related to automation such as automated sinks for hand decontamination [53]. In the context of AV acceptance, the AAM was embraced by Körber, et al [54] who suggested that trust in AVs is a vital precondition for facilitating the acceptance AVs to take advantage of benefits such as human error reduction.…”
Section: ) Trustmentioning
confidence: 99%